HEALTHeBIKES - Smart E-Bike Prototype for Controlled Exercise in Telerehabilitation Programs. - MAYR, Patrick; FALGENHAUER, Markus; MODRE-OSPRIAN, Robert; HOFMANN, Peter; TRANINGER, Heimo; RATH, Michael; SCHREIER, Günter (Studies in Health Technology & Informatics, 2018)
E-Bikes in telerehabilitation programs could be a new intervention for more sustainable rehabilitation results. The aim is to design and build a prototype of an E-Bike usable for rehabilitation - a HEALTHeBIKE. It should avoid over-exercising, work independently of the environment and it should enable cycling in a group despite different reference exercise intensities. To achieve these goals, requirements for this system architecture have been identified. A system architecture including an Arduino microcontroller, an Android smartphone and a telemonitoring platform was presented. A power output regulated proportional-integral controller to adjust the motor assistance has been implemented. A feasibility study with two subjects cycling in a group was performed. Seven test rides on varying terrain (flat, hilly, mountainous and uphill) with the same and different exercise intensities were completed. The mean power output was close to or below the target power output of the cyclist for all test rides with a maximal error of 6.7 % above and 27.6 % below the target. Although the exercise intensities of the two subjects were clearly different, cycling in a group was possible without over-exercising.